"Visita del ministro de Instruccion y Sanidad". F.l.t.r.: Blanco, Mistres Puig, ?. Copied from CNT collection
"Visita del ministro de Instruccion y Sanidad". F.l.t.r.: Blanco, Mistres Puig, ?. Copied from CNT collection.